The Value of Environmental and Health Claims on New Legume Products: A Non-Hypothetical Online Auction - Lemken, Dominic; Knigge, Mandy; Meyerding, Stephan; Spiller, Achim (Sustainability, 2017)
Legumes are valued in agricultural systems, as they can contribute to a more sustainable land use. However, their economic value is low. Despite health and environmental benefits, marketers struggle to communicate the worth of legumes to consumers. We evaluate the worth of health and, in particular, environmental claims that would spread consumers’ awareness of ecological advantages. Utilizing a large consumer sample, we execute binding online auctions. Comparing claim-treated and untreated subjects (between design), we model the price premium that potential customers are willing to pay (WTP) for having pasta in a legume instead of a wheat version. We find that claims may increase the WTP, however, a mix of environmental and health claims is superior to individual claims. Effect sizes suggest that the mix of claims increases the WTP by roughly 35% (20 cents). The link of WTP and food attitudes, such as concern for health in eating habits or social reservations towards legumes, varies depending on whether the green-pea or chickpea pasta was evaluated. A critical perception of legumes’ association with flatulence reduces the WTP. Developing the online auction may enable researchers to increase the external validity of consumer samples. We discuss implications for researchers and marketers.